Археологічні мікрорегіони «Ізяславля»-Ізяслава та «Ізяславля»-Городища - Демидко, С.Ю. (Археологія і давня історія України, 2016)
У статті наведено перелік і короткий опис археологічних об'єктів на території м. Ізяслав Хмельницької обл. Сакраментальный вопрос: который из памятников мы можем интерпретировать как «древнерусский
Изяславль» — городище «Рогнеда» в г. Изяслав или городище «Валы» у с. Городище Шепетовского р-на? Обе
точки зрения имеют своих и защитников, и оппонентов. Отдельная группа исследователей вообще отрицает существование Изаславля в качестве летописного
древнерусского населеного пункта привязывая эти памятники к другим, пока не локализованным волынским городам — Городцу, Каменцу и др. The perennial question is: which site we can interpret
as Iziaslavl’ of Ancient Rus’ Time — Rohneda hillfort
(Iziaslav city) or Valy hillfort (Horodyshche village, Shepetivka
region)? Some of researchers are denied Iziaslavl’
existence as annalistic settlement of Ancient Rus’ Time,
and linked those sites to Volyn’ towns Horodets’, Kamianets’
and others which had not yet localized.
The factor of archeological surrounding (microregion) of
Rohneda and Valy hillforts was not followed up. The process
of territories development and settling structure formation
were ignored. The attempt to fill in the microregional vacuum
around Iziaslav revealed that there were 17 multi-temporal sites dating from Late Paleolithic age to Late Medieval
(11 settlements and 6 tumuli or mound groups). An analysis indicated that in the study of the current research level for
the 12th—14th centuries we cannot reconstruct the reliable situation for the main matter: the size of Ancient Rus’ Time
area of the site and population density. In addition, we cannot determine its ranks (Rohneda’s trading quarters). Under
these conditions it would be premature to make any decision in compare with agglomeration of Valy hillfort.